2015
DOI: 10.1111/adb.12257
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging structural alterations in brain of alcohol abusers and its association with impulsivity

Abstract: Despite the suggestion that impulsivity plays a central role in the transfer from a recreational drug use to a substance use disorder, very few studies focused on neurobiological markers for addiction. This study aimed to identify volumetric alterations in a sample of patients with mild alcohol use disorder with a short history of alcohol use, compared with a control group, and also focused on its association with impulsivity levels. Most magnetic resonance imaging studies have focused on severe alcohol use di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 58 publications
3
25
0
2
Order By: Relevance
“…Our analyses of alcohol intake frequency and RBA indicated that subjects who drank daily or almost daily had a significantly higher RBA compared to those who drank less frequently. Our finding was consistent with previous studies, which showed that heavy alcohol consumption was detrimental to the brain (Asensio et al, 2016;Pfefferbaum et al, 1992;Shokri-Kojori et al, 2017). On the other hand, subjects who drank at special occasions only had on average the lowest RBA of all groups of alcohol consumption frequencies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our analyses of alcohol intake frequency and RBA indicated that subjects who drank daily or almost daily had a significantly higher RBA compared to those who drank less frequently. Our finding was consistent with previous studies, which showed that heavy alcohol consumption was detrimental to the brain (Asensio et al, 2016;Pfefferbaum et al, 1992;Shokri-Kojori et al, 2017). On the other hand, subjects who drank at special occasions only had on average the lowest RBA of all groups of alcohol consumption frequencies.…”
Section: Discussionsupporting
confidence: 93%
“…It has also been reported that patients with alcohol use disorder show decreased regional grey and white matter volumes in the medial-prefrontal and orbitofrontal cortices. The loss of brain gray and white matter volume accelerates with aging in chronic alcoholics (Asensio et al, 2016;Pfefferbaum et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These brain regions were closely associated with impulsivity as mentioned before [39, 40]. Given that impulsivity is multi-dimensional construct [7] and different aspects of impulsivity may reflect separate processes [6].…”
Section: Discussionmentioning
confidence: 78%
“…The mPFC was involved in cognitive control that monitored ongoing actions and performance outcomes and subsequent adjustments of behavior and learning to acquire flexible goal-directed behavior [42]. The deficits in this area may lead an impaired cognitive control over emotional and compulsive reactions [39]. Recent theories suggested that the ACC served as a monitoring role for the detection of erroneous or error-prone actions, together with the mPFC involved in the cognitive control [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…2013b; Walhovd et al, 2012), including a smaller study of patients diagnosed with DSM-IV alcohol abuse and matched controls (Asensio et al., 2015), we did not find that gmPVE correlated negatively with self-reported impulsive behavior, either as a function of our BS/IMP component (consisting of significant loadings from scales reflecting boredom susceptibility, impulsive acts, antisocial behaviors, social disinhibition, and a desire to seek out unusual experiences), or when looking specifically at the Impulsivity subscale of the Eysenck I 7 inventory. The Impulsivity subscale of the Eysenck I 7 inventory did, however, correlate positively with bilateral gmPVE in lateral/posterior orbital cortex and insula.…”
Section: Discussionmentioning
confidence: 99%